History of hydroacoustic surveys of small pelagic fish species in the European Mediterranean Sea - LEONORI, IOLE; TIČINA, VJEKOSLAV; GIANNOULAKI, MARIANNA; HATTAB, TAREK; IGLESIAS, MAGDALENA; BONANNO, ANGELO; COSTANTINI, ILARIA; CANDUCI, GIOVANNI; MACHIAS, ATHANASSIOS; VENTERO, ANA; SOMARAKIS, STYLIANOS; TSAGARAKIS, KONSTANTINOS; et al. (Mediterranean Marine Science, 2021)
The study of small pelagic fish by hydroacoustic methods in the Mediterranean Sea began in the Adriatic in the 1950’s. Since 2009, internationally coordinated, extensive, regular surveys have been conducted in the framework of the MEDIAS - Mediterranean International Acoustic Surveys – action, under the EU Data Collection Framework, to provide inputs for the management of small pelagics, particularly European anchovy (Engraulis encrasicolus) and European sardine (Sardina pilchardus). The surveys cover EU Mediterranean waters and monitor the distribution and abundance of small pelagic species using a common protocol. The hydroacoustic surveys, historically conducted by each Country separately, have since been standardized and harmonized. This is a review of the evolution of the surveys from the beginning up to the present and discusses the future prospects. It reports the historical time series of anchovy, sardine and other small pelagics in different areas and describes the spatial and temporal distribution of small pelagic species in decadal maps of the major areas of their distribution in the European Mediterranean Sea. Furthermore, it discusses the use of MEDIAS data for stock assessment purposes, the collection of auxiliary information for an ecosystem-based management approach, the need for further standardization and future challenges.